P-16 A service evaluation: patient, relative and staff experiences of virtual visiting during the COVID-19 pandemic at cardiff and the vale's marie curie hospice. (20th March 2022) - Ray, Isabelle; Seaman, Siwan
Abstract : Background: The Covid-19 pandemic has had a profound impact on health services, including the implementation of measures to maintain safe social-distancing to reduce viral spread. This has included the visiting restrictions in hospitals and hospices and a subsequent increase in demand for virtual consultations and visiting. 1 2 This has impacted how in-patients, relatives and staff communicate daily. Aims: To investigate staff, patient and relative experiences of virtual visiting during Covid-19 in a hospice and to provide recommendations to improve current virtual visiting practices. Methods: A service evaluation was conducted in March 2021 using mixed methods. Interviews were held with current in-patients and two surveys were created with the aims of collecting patient, relative and staff experiences of virtual visiting. Participants were recruited in person and via emails and social media posts. Data collection was anonymous, containing no participant identifiable information. Results: All patients, relatives and staff who took part either in the interviews or surveys had partaken in virtual visiting using a range of personal and hospice devices. Analysis of qualitative data uncovered four key themes: the importance of keeping connected, technological literacy and usability, methods of virtual visiting and challenges with connectivity, time and equipment accessibility. Discussion and Conclusions: Limited literature has been published on virtual visiting experiences of staff, relatives and patients during Covid-19 in palliative care. This project demonstrates the benefits of virtual visiting during a time where in-person visiting is restricted, and the inevitable drawbacks of relying on technology for communication. Finding ways to overcome challenges relating to digital illiteracy and connectivity issues will help to improve virtual visiting communication at the hospice so that all can keep connected and updated. Suggestions included dedicated staff or volunteers to assist with virtual visiting and accessible instructions for patients outlining how to connect devices to the internet. References: GOV.Wales. 2020. Hospital visiting during the coronavirus outbreak: guidance. Available: https://gov.wales/hospital-visiting-during-coronavirus-outbreak-guidance-html. Last accessed 8th April 2021. Hawkins JP, Gannon C, Palfrey J. Virtual visits in palliative care: about time or against the grain?. BMJ Supportive & Palliative Care 2020;10 (3):331–336.